Respostas

2013-10-29T16:23:36-02:00
{4x+2y=4.....(:2) => 2x+y =2.....y=2-2x
{3x-4y=0
3x-4(2-2x) =0
3x-8+8x=0
11x=8
x=8/11

y=2-2x = 2-2(8/11)= 2 -16/11 = 22-16/11 = 6/11
2013-10-29T16:54:07-02:00
2x - 4y = 5
3x + 2y = 8

2x = 5 + 4y
x = 5 + 4y 
         2
3 (5 + 4y) + 2y = 8
      2
15 + 12y +2y = 8
     2
mmc = 2
15 + 12y + 4y = 16
16y = 16 - 15
16y = 1
y =  1   
      16
Para encontrar o valor de x, basta substituirmos o valor de y em qualquer uma das equações; na 1ª por exemplo.
2x - 4y = 5
Substituindo fica:
2x - 4 (  1  ) = 5
            16
2x -  4  =  5
       16
2x = 5 +  4  
             16
mmc = 16
2x = 80 + 4 
          16
2x = 84  => simplificando fica: 21
        16                                  4
x = 21 : 2
       4
x = 21 x 1 
       4    2 
x = 21
       8
Resposta:
x = 21  ou 2,625
       8      
y =   1  ou 0,0625 
       16
1 1 1